Management of Anterior Spacing with Peg Lateral by Interdisciplinary Approach : A Case Report - Gupta, Sanjay Prasad (Orthodontic Journal of Nepal, 2019)
Anterior spacing is a common esthetic problem of patient during dental consultation. The most common etiology include tooth size and arch length discrepancy. Maxillary lateral incisors vary in form more than any other tooth in the mouth except the third molars. Microdontia is a condition where the teeth are smaller than the normal size. Microdontia of maxillary lateral incisor is called as “peg lateral”, that exhibit converging mesial and distal surfaces of crown forming a cone like shape. A carefully documented diagnosis and treatment plan are essential if the clinician is to apply the most effective approach to address the patient’s needs. A patient sometimes requires a multidisciplinary approach to correct the esthetics and to improve the occlusion. This case report describes the management of an adult female patient with a proclined upper anterior teeth, upper anterior spacing, deep bite and peg shaped upper right lateral incisor tooth through orthodontic and restorative treatment approach.